Haff Syndrome and challenges to public health: an integrative review (Research, Society and Development, 2023)
Objective: To describe the available national and international scientific evidence related to the challenges caused to public health concerning cases and outbreaks of Haff's Syndrome. Methodology: The study was an integrative review, in which the PICo strategy was used to elaborate the research question and articles from the national and especially international literature were used to compose the sample.  Results: Some obstacles were found: significant increase in the number of Haff cases (51 and 85 cases); expansion of the outbreak to almost all regions of Brazil (North: 82.35%; Northeast: 27.05%); challenge of tracking and reporting; non-identification of the toxin responsible and negligence of the authorities regarding food poisoning, especially by Foodborne Diseases. Discussion: The studies show that the greatest number of cases of Haff's disease has been through the consumption of freshwater fish. There is not much information about the disease and this is an alarming factor, since the number of notifications around the world has been increasing since its discovery, besides making diagnosis and treatment difficult. Conclusion: The expansion of studies on the importance of the notification of cases will contribute to the monitoring and proper operational procedure, aiming to combat this public health problem.